A Bayesian phase I/II design to determine subgroup‐specific optimal dose for immunotherapy sequentially combined with radiotherapy. (26th September 2022) - Guo, Beibei; Zang, Yong; Lin, Li‐Hsiang; Zhang, Rui
Abstract: Sequential administration of immunotherapy following radiotherapy (immunoRT) has attracted much attention in cancer research. Due to its unique feature that radiotherapy upregulates the expression of a predictive biomarker for immunotherapy, novel clinical trial designs are needed for immunoRT to identify patient subgroups and the optimal dose for each subgroup. In this article, we propose a Bayesian phase I/II design for immunotherapy administered after standard‐dose radiotherapy for this purpose. We construct a latent subgroup membership variable and model it as a function of the baseline and pre‐post radiotherapy change in the predictive biomarker measurements. Conditional on the latent subgroup membership of each patient, we jointly model the continuous immune response and the binary efficacy outcome using plateau models, and model toxicity using the equivalent toxicity score approach to account for toxicity grades. During the trial, based on accumulating data, we continuously update model estimates and adaptively randomize patients to admissible doses. Simulation studies and an illustrative trial application show that our design has good operating characteristics in terms of identifying both patient subgroups and the optimal dose for each subgroup.